2016
DOI: 10.1016/j.celrep.2015.12.069
|View full text |Cite
|
Sign up to set email alerts
|

The 11S Proteasome Subunit PSME3 Is a Positive Feedforward Regulator of NF-κB and Important for Host Defense against Bacterial Pathogens

Abstract: SUMMARY The NF-κB pathway plays important roles in immune responses. Although its regulation has been extensively studied, here, we report an unknown feedforward mechanism for the regulation of this pathway by Toll-like receptor (TLR) ligands in macrophages. During bacterial infections, TLR ligands upregulate the expression of the 11S proteasome subunit PSME3 via NF-κB-mediated transcription in macrophages. PSME3, in turn, enhances the transcriptional activity of NF-κB by directly binding to and destabilizing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 57 publications
0
30
0
Order By: Relevance
“…All cells were grown in a 37°C incubator supplied with 5% CO 2 . BMDMs and PEMs were prepared as described previously (Sun et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…All cells were grown in a 37°C incubator supplied with 5% CO 2 . BMDMs and PEMs were prepared as described previously (Sun et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Overexpression of AX2R might mutate these phosphodegron motifs, abolishing the degradation and ubiquitination of KLF2 [23, 30]. Although studies have shown that KLF2 mRNA expression is regulated by various signals, including stress, growth factors and cytokines in endothelial cells, the mechanism that regulates KLF2 abundance at the posttranslational level has remained largely unknown [31, 32]. How KLF2 protein stability is regulated in endothelial cells has also remained unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Mouse PMs were prepared in our laboratory following procedure described previously. 25 In brief, C57BL/6 J or ICER knockout mice and littermates were injected with 3% sterile thioglycollate (Sigma, St. Louis, MO, USA) intraperitoneally (3 ml per mouse). After 3 days, mice were euthanized, and RPMI medium was injected intraperitoneally and then retrieved.…”
Section: Discussionmentioning
confidence: 99%